PENGARUH TINGKAT KEPERCAYAAN DAN KEPUASAN ATAS KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH TABUNGAN PADA BANK NAGARI CABANG PASAR RAYA PADANG - Ira Dwiana; Yunia Wardi (Program Studi Magister Manajemen, 2013)
The objective of this research is to tested the influence of trust toward customer loyality and The influence of the satisfaction of service quality toward customer loyalty. The primary data is obtained from the customer of Bank Nagari Pasar Raya Padang Trust represented the convinience to make long term relationship to build positive performance. Service quality including service which was given by Bank Nagari Pasar Raya Padang involved how they gave service. Data tested and analyzed with Multiple Analysis Regression Linier. The method of sampling is accidental sampling. The population is the customer of Bank Nagari Pasar Raya Padang. The sample consisted of 100 respondents. The result of this research shows that both hiphothesys were proved. There is a positive effect on trust toward customer loyality, there is a positive effect on satisfaction of service quality toward customer loyality. Key word: Trust, Satisfaction of service quality, customer loyality.